BIO-EXPLOITATION STATUS OF BOMBAY DUCK (Harpadon nehereus HAMILTON, 1822) ON TRAWL FISHERY IN TARAKAN WATERS - Duto Nugroho; Ria Faizah; Andhika P. Prasetyo; M. Badrudin (Indonesian Fisheries Research Journal, 2015)
North Kalimantan Province, notably Tarakan City marine waters, is one of the important fishing ground in boundary area among Sulu Sulawesi Marine Ecoregion. It produces approximately 100 mt/annum of Bombay duck (Harpadon nehereus) with valued of US$ 750,000. The sustainability of this fishery is a crucially concern given the following: substantial economic contribution, significant dependence of small-scale fishers on this species for their livelihoods. The fishing intensities considerable and growing threats to their habitats. To evaluate the vulnerability of individual species to over exploitation, the spawning potential ratio (SPR) approach applied to describe the status of its existing fisheries. This approach provides the ability to determine fishing mortality as reference points to enhance its sustainability. The objective of this study is to understand this fish biomass resilience to harvesting. The calculated SPR based on the value of estimated length of first capture or Lc at 208 mm is equivalent to the SPR of 28%. With a base line of stocks are generally thought to risk recruitment declining when SPR <20%, recent finding indicated that the existing fishery can be generally described as nearly fully exploited. In recognition of this sector’s has an ecological importance and socio-economic significance, the sustainable development of Bombay duck fisheries should be initiated through developing local fishery committee to provide a their local fishery management plan.